George Sumerell plays the accordion in the John Meredith folklore collection - Sumerell, George, 1932-; Meredith, John, 1920-2001.; Willis, Rob, 1944- (1991)
Folkloric recording.
Irish washerwoman -- Unidentified (jig) -- Ring the bell, watchman -- Over the waves -- You can be true, dear -- Old Black Joe (set tune) -- Swanee River (set tune) -- Unidentified (varsovianna) -- Little brown jug (polka) -- Mary Black (polka; aka Early in the morning) -- Whistling Rufus -- Music, music, music -- MacNamara's Band -- Dan Murphy's door -- 15. Lovely bunch of coconuts -- Tipperary -- Home sweet home -- Prize pig jig (learnt from Dave de Hugard) -- Peggy O'Neil (waltz) -- Bless 'em all -- Two little girls in blue -- After the ball -- Tipperary.
Interviewed and recorded by John Meredith and Rob Willis.
Recorded on May 17, 1991 at Bemboka, N.S.W.
Digital master available
Keywords: Sumerell, George, -- 1932- -- Interviews; Folk musicians -- New South Wales -- Bemboka -- Interviews; Accordion music; Folk music -- New South Wales -- Bemboka